Analysis of Kidney Function Tests as Predictor of Mortality in COVID-19 - Sitti Rahma; Yuyun Widaningsih; Liong Boy Kurniawan; Fitriani Mangarengi (INDONESIAN JOURNAL OF CLINICAL PATHOLOGY AND MEDICAL LABORATORY, 2023)
Cytokine release syndrome and Acute Respiratory Distress Syndrome (ARDS) increase the incidence of Acute Kidney Injury (AKI) in COVID-19 patients, which is associated with a poor prognosis and risk of death. The purpose of this study was to analyze urea, creatinine, and eGFR values as predictors of mortality in COVID-19 patients. A retrospective cohort study was carried out using secondary data from medical records of 311 COVID-19 patients who were treated at the Hasanuddin University State Higher Education Hospital from August 2020 to August 2021. Data were analyzed using the Mann-Whitney test, Chi-Square, and Logistic Regression. The risk of mortality for COVID-19 patients with urea levels > 53 mg/dL was 5.128 times higher than that of urea levels ‰  53 mg/dL (OR=5.128; CI =2.530 – 10.391, p<0.001). The risk of mortality for COVID-19 patients with creatinine levels  > 1.3  mg/dL was 2.696 times higher than that of creatinine levels  ‰  1.3  mg/dL (OR= 2.696; CI = 1.330 – 5.463, p<0.001). The risk of mortality in COVID-19 patients with an eGFR <  90  mL/min/1.73 m2  was  3.692 times higher than that of an eGFR ‰ 90 mL/min/1.73 m2 (OR=3.692; CI = 2.134 – 6.389, p<0.001). Multiple logistic regression analysis showed that urea and eGFR were better predictors of mortality than creatinine (OR= 0.374, p=0.002 vs. OR 0.344, p=0.007 vs. OR 1.192, p=0.694). The COVID-19 patient group with high serum urea and creatinine levels and low eGFR values had a greater risk of mortality compared to the group of patients who had normal results. Urea levels and eGFR values were better predictors of mortality than serum creatinine.